Modelling height-diameter relationship for Chir pine trees - Sharma, RP (Banko Janakari, 2010)
Tree height-diameter relationship can be used as an important input component in growth and yield models, and description of stand dynamics. This study aims at establishing robust height-diameter models for Chir pine (Pinus roxburghii) trees using regression techniques. Among the twelve non-linear models fitted to height-diameter data from twentythree Chir pine stands in Parbat and Shyangja districts, Hossfeld's model accounted for the largest proportion of height variations (R2adj = 86%), and appeared to be biologically most realistic. This model can be applied to similar stand conditions from where study data were procured. Keywords: Chir pine; height-diameter models; model evaluation; stand attributes DOI: 10.3126/banko.v19i2.2978 Banko Janakari, Vol. 19, No.2 2009 pp.3-9